(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As we know, one of the lifelong learning forms, which is the correspondence education, has received a wide circulation in our country. However, we have recently mentioned that the type of education should be adapted to modern conditions. As a way out from this situation, the article analyzed the specifics of the distance and supplementary education in the world and the stages of development. Mechanisms of application of existing educational technologies in Azerbaijan were studied. In order to achieve the goals mentioned in the article, the relevant legislation of Azerbaijan has been prepared and recommendations for institutional reforms have been prepared. In the context of globalization, the development of new technologies has negative effects, though there are positive effects. The strengthening of globalization leads to the inequality of development among countries, the sharp differences in the living standards of the population, the escalation of language, religion, traditions and, ultimately, the weakening of national state institutions. In this case, the protection and development of the state language is of great importance and special attention should be paid to this problem. At the end of the article, we came to the problem from another aspect, and we believe that if we use the right technologies properly and precisely, it can be achieved through the promotion of mother tongue. Our compatriots living abroad will be able to acquire new knowledge and will not forget and develop their mother tongue with effective use of remote training technologies. Millions of our compatriots living abroad will be able to benefit from these advantages. In order to achieve this, it is important to use the modern IT technologies’ innovations as well as the effective use of language teaching methods for language development carried out by linguists. We believe that there is a relationship between these two factors, and when analyzing lifelong learning issues, there is a need for two aspects. At the end, it should be noted that we have to analyze the problem from different perspectives and make suggestions.